Ocorrência de Trichospilus diatraeae (Hym.: Eulophidae) em broca-das-cucurbitáceas, no Brasil - Melo, Ricardo L de; Pratissoli, Dirceu; Polanczyk, Ricardo Antônio [UNESP]; Tavares, Marcelo; Milanez, André M; Melo, Débora F (Associação Brasileira de Horticultura, 2011)
Este trabalho tem como objetivo registrar a primeira ocorrência, no Brasil, do parasitóide de pupas Trichospilus diatraeae (Cherian & Margabandhu, 1942) (Hymenoptera: Eulophidae) na broca-das-cucurbitáceas, Diaphania hyalinata (L.) (Lepidoptera: Pyralidae). A espécie T. diatraeae já foi relatada no Brasil em pragas da gravioleira no Distrito Federal e eucalipto nos estados de Minas Gerais e São Paulo. No sistema produtivo da abóbora D. hyalinata é reconhecidamente uma praga importante por causar sérios prejuízos em função das injúrias provocadas em diferentes partes da planta. A ocorrência do parasitóide foi registrada em pupas coletadas no campo, localizado no campus experimental do Centro de Ciências Agrárias da Universidade Federal do Espírito Santo (UFES), no município de Alegre-ES.

This study aims to record the first occurrence in Brazil of the parasitoid pupae Trichospilus diatraeae (Cherian & Margabandhu, 1942) (Hymenoptera: Eulophidae) on the melonworm, Diaphania hyalinata (L.) (Lepidoptera: Pyralidae). The specie T. diatraeae has been reported in pests of the soursop in the Distrito Federal, Brazil and eucalyptus in the Brazilian States of Minas Gerais and São Paulo. In the production system of pumpkin D. hyalinata is recognized as a significant pest which causes serious losses as a result of injuries caused in different parts of the plant. The occurrence of the parasitoid was recorded in pupae collected in the field, located on the campus of the Center of Agrarian Sciences, Federal University of Espirito Santo, Alegre Espirito Santo State, Brazil.
Occurrence of the parasitoid Trichospilus diatraeae (Hym.: Eulophidae) in melonworm, in Brazil
Keywords: Diaphania hyalinata; parasitism; Biological control; Diaphania hyalinata; Parasitismo; Controle biológico